A Versatile Pep-CPDs Nanoprobe for Rapid Detection of mTBI Biomarker in Clinical Instances and Safe Fluorescence Imaging In Vivo for Improved Weight-Drop Mouse Model - Shi, Jian; Li, Xingmei; Cavagnaro, María José; Cai, Jifeng; Zhang, Changquan; Li, Na (Frontiers in Bioengineering and Biotechnology, 2022)
Mild traumatic brain injury (mTBI) is the most common form of traumatic brain injury; however, it is the most difficult to be accurately identified in the early stage because it lacks more reliable biomarkers and detection methods. This study proposes a highly efficient system to detect a molecular biomarker for the early diagnosis of mTBI. The system was prepared by a lower cytotoxic peptide-modified fluorescent nanoprobe based on carbon polymer dots (pep-CPDs) with outstanding imaging capabilities. In vitro and in vivo tests were explored to the efficiency of pep-CPDs, inferring the good performances of cellular fluorescence imaging and in vivo imaging of mice. Moreover, an application of the versatile pep-CPDs on detecting the mTBI biomarker S100-β detection in a novel improved weight-drop mTBI mouse model and human blood samples has been successfully established. Overall, all these results indicate that the pep-CPD system is sensitive, rapid, non-toxic, and reliable for mTBI diagnosis compared with traditional detection methods. It shows a great potential in clinical and translational research and practical applications.